Extract of Mallotus oppositifolius (Geiseler) Müll. Arg. increased prefrontal cortex dendritic spine density and serotonin and attenuated para-chlorophenylalanine-aggravated aggressive and depressive behaviors in mice - Kukuia, Kennedy K.E.; Appiah, Frimpong; Dugbartey, George J.; Takyi, Yaw F.; Amoateng, Patrick; Amponsah, Seth K.; Adi-Dako, Ofosua; Koomson, Awo E.; Ayertey, Frederick; Adutwum-Ofosu, Kevin K. (Frontiers in Pharmacology, 2022)
Background/Aim: Depression-related aggression is linked to serotonin (5-HT) and dendritic spine alterations. Although Mallotus oppositifolius extract (MOE) has potential for reducing this effect, its specific role remains uncertain. Herein, we evaluated this potential and associated alterations in the brain. Methods: A standard resident-intruder model of para-chlorophenylalanine (pCPA)-induced depression-associated aggression in male ICR mice was used. The resident mice received pCPA (300 mg/kg, i. p.) for 3 consecutive days while saline-treated mice served as negative control. The pCPA aggressive mice were subsequently treated orally with either MOE (30, 100, 300 mg/kg), fluoxetine (20 mg/kg), tryptophan (20 mg/kg) or saline (untreated pCPA group) for 28 days. Locomotor activity was assessed using open field test. Serotonin (5-HT) levels in mice brain and phytochemical fingerprint of MOE were determined by high performance liquid chromatography (HPLC) while gas chromatography-mass spectrometry (GC-MS) was used to identify constituents of MOE. Dendritic spine density and morphology were evaluated using Golgi-Cox staining technique and analyzed with ImageJ and Reconstruct software. Results: Administration of pCPA induced aggressive behavior in mice, evidenced by increased attack behaviors (increased number and duration of attacks), which positively correlated with squeaking and tail rattling. MOE treatment significantly reduced these characteristics of aggression in comparison with vehicle (non-aggressive) and untreated pCPA groups (p < 0.001), and also reduced social exploration behavior. Although the behavioral effects of MOE were comparable to those of fluoxetine and tryptophan, these effects were quicker compared to fluoxetine and tryptophan. Additionally, MOE also markedly increased 5-HT concentration and dendritic spine density in the prefrontal cortex relative to vehicle and untreated pCPA groups (p < 0.05). Interestingly, these behavioral effects were produced without compromising locomotor activity. GC-MS analysis of the MOE identified 17 known compounds from different chemical classes with anti-inflammatory, antioxidant, neuroprotective and antidepressant activities, which may have contributed to its anti-aggressive effect. Conclusion: MOE decreased depression-associated aggressive behavior in mice via increased 5-HT concentration and dendritic spine density in the prefrontal cortex. The MOE-mediated effects were faster than those of fluoxetine and tryptophan. Our finding suggests that MOE may have clinical promise in decreasing aggressive and depressive behaviors.